Single-step discovery of high-affinity RNA ligands by UltraSelex - Zhang, Yaqing; Jiang, Yuan; Kuster, David; Ye, Qiwei; Huang, Wenhao; Fürbacher, Simon; Zhang, Jingye; Doll, Pia; Lin, Wenjun; Dong, Siwei; Wang, Hui; Tang, Zhipeng; et al. (Nature chemical biology, 2025)
Aptamers, nucleic acid ligands targeting specific molecules, have emerged as drug candidates, sensors, imaging tools and nanotechnology building blocks. The predominant method for their discovery, systematic evolution of ligands by exponential enrichment, while successful, is laborious, time-consuming and often results in candidates enriched for unintended criteria. Here we present UltraSelex, a noniterative method that combines biochemical partitioning, high-throughput sequencing and computational signal-to-background rank modeling for discovering RNA aptamers in about 1 day. UltraSelex identified high-affinity RNA aptamers capable of binding a fluorogenic silicon rhodamine dye and two protein targets, the SARS-CoV-2 RNA-dependent RNA polymerase and HIV reverse transcriptase, enabling live-cell RNA imaging and efficient enzyme inhibition, respectively. From the ranked sequences, minimal aptamer motifs could be easily inferred. UltraSelex provides a rapid route to reveal new drug candidates and diagnostic tools.
Online veröffentlicht: 31. März 2025
Gesehen am 22.10.2025